Spatial Distribution of Macrophages During Callus Formation and Maturation Reveals Close Crosstalk Between Macrophages and Newly Forming Vessels - Stefanowski, Jonathan; Lang, Annemarie; Rauch, Ariana; Aulich, Linus; Köhler, Markus; Fiedler, Alexander F.; Buttgereit, Frank; Schmidt-Bleek, Katharina; Duda, Georg N.; Gaber, Timo; Niesner, Raluca A.; Hauser, Anja E. (Frontiers in Immunology, 2019)
Macrophages are essential players in the process of fracture healing, acting by remodeling of the extracellular matrix and enabling vascularization. Whilst activated macrophages of M1-like phenotype are present in the initial pro-inflammatory phase of hours to days of fracture healing, an anti-inflammatory M2-like macrophage phenotype is supposed to be crucial for the induction of downstream cascades of healing, especially the initiation of vascularization. In a mouse-osteotomy model, we provide a comprehensive characterization of vessel (CD31+, Emcn+) and macrophage phenotypes (F4/80, CD206, CD80, Mac-2) during the process of fracture healing. To this end, we phenotype the phases of vascular regeneration – the expansion phase (d1 - d7 after injury) and the remodeling phase of the endothelial network, until tissue integrity is restored (d14 - d21 after injury). Vessels which appear during the bone formation process resemble type H endothelium (CD31hiEmcnhi), and are closely connected to osteoprogenitors (Runx2, Osx) and F4/80+ macrophages. M1-like macrophages are present in the initial phase of vascularization until day 3 post osteotomy, but they are rare during later regeneration phases. M2-like macrophages localize mainly extramedullary, and CD206+ macrophages are found to express Mac-2+ during the expansion phase. VEGFA expression is initiated by CD80+ cells, including F4/80+ macrophages, until day 3, while subsequently osteoblasts and chondrocytes are main contributors to VEGFA production at the fracture site. Using Longitudinal Intravital Microendoscopy of the Bone (LIMB) we observe changes in the motility and organization of CX3CR1+ cells, which infiltrate the injury site after an osteotomy. A transient accumulation, resulting in spatial polarization of both, endothelial cells and macrophages, in regions distal to the facture site, is evident. Immunofluorescence histology followed by histocytometric analysis reveals that F4/80+CX3CR1+ myeloid cells precede vascularization.